Malaysian oral health literacy training package @ Celik Literasi Kesihatan Mulut Malaysia (CeLiK-M). module 4: healthcare system navigation - Rani, Haslina; Che Musa, Muhd Firdaus; Zabha, Azliza; Ruslan, Ruzawani; Mohd Jeffry, Sabrina Julia; Abdul Manab, Enny Esdayantey; Kamarozaman, Dewi Mayang Sari (Oral Health Programme, Ministry of Health, 2026)
This module is part of a training package that has been carefully designed as a trainer’s resource to strengthen oral health literacy among oral healthcare personnel in Malaysia. The primary objective of the package is to raise awareness on the importance of oral health literacy and to enhance the essential skills required to address oral health literacy challenges in professional practice. The module addresses oral health literacy from systems perspective, focusing on how healthcare environments and services can either support or hinder patients’ ability to access and utilise oral healthcare. Participants will be introduced to the concept of healthcare system navigation and the importance of creating supportive oral healthcare environments that are responsive to patients’ literacy needs. Through this module, participants will learn to identify strengths, gaps, and barriers within the oral healthcare system, including organisational processes, communication practices, and physical environments. The module also equips participants with skills to assess literacy-related aspects of healthcare settings and to propose practical recommendations for improving system level support, thereby enhancing patient access, understanding, and continuity of care.